The Economic Impact of the Covid-19 Pandemic Related to Bahrain's Bankruptcy Law - Nashat Mahmoud Jaradat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to address the concerns relating to the economic impact of the Covid-19 Pandemic in the Kingdom of Bahrain by observing the preventive measures taken by the government to ensure minimal economic deterrence. Furthermore, the paper shall also address the role and the position of the Reorganization and Bankruptcy Law no. (22) 2018 of Bahrain in light of the economic duress faced by the businesses in Bahrain and the role played by the government and financial institutions in resolving matters relating to bankruptcy that would be more prevalent due to the Covid-19 Pandemic. The importance of the research is highlighted by highlighting the economic impact and the mechanism of bankruptcy procedures followed in Bahrain, especially in light of the global economic crisis it is facing due to the Covid-19 pandemic. The study aims to clarify the laws related to bankruptcy with a study of the current situation in Bahrain. As there is no previous study regarding the economic effects on the movement of trade in the Kingdom of Bahrain in light of the Corona pandemic and the role of bankruptcy law in that. It was also clarified through this study to the close relationship between local legislation and international legislation and agreements related to this subject.